Beyond pink and blue: a content and discourse analysis of gender representation in visuals and texts of bilingual Thai-English children’s books - Bandita Santikul (Penerbit Universiti Kebangsaan Malaysia, 2025)
While gender representation has been extensively explored in international contexts, there is limited understanding of how multilingual literature, especially in Thailand, where gender roles are strictly defined, may influence young readers' perceptions of these roles. The present study addresses that unexplored area by investigating gender portrayal in bilingual Thai-English children’s books, focusing on gender patterns, examining verb types associated with males and females, and determining if these books expand or confirm traditional gender norms. The qualitative content analysis was employed to examine key gender patterns in the books using Reform’s (2016) gender analysis strategies for children’s books. As for the quantitative analysis, verb element types and their frequency were identified using Johnson and Young’s (2002) verb taxonomy. Both methods lead to the conclusion of whether the books reinforce or challenge traditional gender norms. Regarding the visual analysis, the illustrations exhibited some diversity by presenting genders in varied ways. They predominantly depicted traditional gender roles for women and men. However, the findings of the text analysis revealed that girl-oriented conversations occurred more frequently than boy-oriented and boy-and-girl-oriented ones. In all cases, action verbs were used the most, followed by limited activity verbs and feeling and nurturing verbs. The findings highlighted a positive trend in gender representation in children’s books and encouraged educators, authors, and curriculum developers to be aware of gender stereotyping in the books.